INVESTMENT IN POWER INDUSTRY: GLOBAL PERSPECTIVES AND OPPORTUNITIES - D. Voyko (Вестник университета)
Investments in power generation are kind of «trapped capital»: it’s impossible to stop them because promising prospects both in terms of cash flows and in part of the capitalization of energy companies; there is no reason continue being due to the constantly changing investment «landscape» and preferences of a consumer of electricity. Worldwide, the increase in total investment in the electricity sector occurs in the background of the «struggle» of companies implementing the generation of electricity from renewable sources and companies that receive electricity in the traditional way. The current state of the investment market in the power industry, the basic prerequisites for this and the prospects and challenges facing governments and private companies in the energy sector has been described.